Римські форти на території Ольвійської держави - Козленко, Р.О. (Археологія, 2016)
До наукового обігу вводяться результати перших досліджень нових римських фортів на території Ольвійської держави, розташування яких свідчить про існування на теренах Нижнього Побужжя системи укріплень лімесного типу. The article presents the results of preliminary research at recently discovered Roman military camps on the territory of Olbian chora. Their location testifies for the existence of the defensive system of limes type in the Lower Buh River region. Non-standard planning of one of the forts indicates that there were two co-existent sub-units of the Roman army in it which held strategically important position in the Steppe, at the south-western borders of the Olbian state. The materials found during the excavations allowed the author to date the erecting of the fort by the second half of the 1st century AD. It coincides with a series of important historic events in the Black Sea north region. Besides, the chronological span and the type of fortification building allow connecting the fort with the auxiliary troops (auxilia) mentioned in Olbian Decree from Manhup, which were sent to help the Olbians from the Moesia Province in the absolute necessity moment under outside appointed pressure of definite groups of the nomadic tribes. The commander of this vexillatio was probably M. Aemilius Lucius Severinus, a centurion of Legio I Italica. В статье представлены результаты первых работ на недавно выявленных римских военных лагерях на территории Ольвийской хоры. Их расположение свидетельствует о существовании в Нижнем Побужье системы укреплений лимесного типа. Нестандартная планировка одного из фортов указывает на два сосуществовавших в нем подразделения римской армии, которые удерживали стратегически важную позицию в степном пространстве, на северо-западной границе Ольвийского государства. Обнаруженный в ходе раскопок материал позволяет датировать сооружение крепости второй половиной I в., что совпадает с рядом важнейших исторических событий в Северном Причерноморье. Кроме того, данный хронологический отрезок и характер возведенного укрепления позволяет связать его с упоминаемыми в ольвийском декрете из-под Мангупа вспомогательными отрядами (auxilia), присланными в помощь ольвиополитам из провинции Мезия в момент крайней необходимости, под внешним давлением определенных групп кочевых племен. Командиром данной вексилляции мог быть центурион I Италийского легиона М. Эмилий Люций Северин.